Using web-based language reference tools to solve linguistic problems in academic writing among Iranian postgraduate students in a Malaysian public university - Shakibkotamjani, Sedigheh (2017)
Electronic literacy plays a major role in the rapidly changing environment of the language learning and teaching. Corpus consultation or learner concordancing has been acknowledged to enhance second language writing and language pedagogy by promoting data-driven learning and providing authentic examples. Onlineconc.com website has been developed as the main research instrument. It consists of multiple reference resources such as concordancers, thesaurus, online dictionaries and search engines such as Google and Google Scholar; they act as cognitive tools for solving linguistic problems while writing academically in English. Participants of this study were six postgraduate students. This study is based on a qualitative case study, which was supported by quantitative data. Various sources of data, such as surveys, stimulated recalls, interviews, screen recordings, and query logs were employed to achieve in-depth descriptions of participants’ corpus consultation pattern. This study consists of two phases, in the first phase 27 postgraduate students were asked to respond to surveys. They were trained how to use different resources in Onlineconc website. Moreover, the researcher raised students’ awareness regarding collocation and lexico-grammatical words. In the second phase, six motivated participants volunteered for a case study. All six participants recorded their laptop screens while consulting with Onlineconc while composing their research paper or dissertation. The results revealed that the process of composing was facilitated by consulting with the combination of reference resources. The findings of various data sources indicated that participants were able to solve 85% of their lexical and grammatical problems that led to appropriate text formulations and revisions. Findings from interviews and stimulated recalls, revealed that concordancing along with other online resources have resulted in more accuracy. Participants of this study found reference resources as useful cognitive tools to verify their intuitive linguistic hypotheses for negotiating meaning, and acquiring authentic language.